Rainfall Forcasting in Medan City Using Singular Spectrum Analysis (SSA) - Silvia Agustina; Fadhilah Fitri; Dodi Vionanda; Admi Salma (Departemen Statistika Universitas Negeri Padang, 2023)
Singular spectrum analysis is a time series analysis that can be used for data that has seasonal effects. Rainfall is one example that has a seasonal effect. High rainfall has an impact on natural disasters such as floods. Medan city is the capital city of North Sumatra province which has quite high rainfall and is a lowland area, so it has the potential for flooding. Rainfall forecasting can be done as disaster mitigation. The forecasting method used is SSA. The MAPE forecasting accuracy value obtained is 15.5% and the tracking signal is within tolerance limits, so that it can be concluded that the forecasting is done well.